Modelling soil erosion and sediment transport of the Nqoe River Catchment at 'Muela - Khaba, Liphapang (2018)
This study assesses the dynamics of soil loss rates of the Nqoe River Catchment. The assessment is made by numerical modeling of the stream water levels and flow, as well as the suspended and bed-load sediment. Literature states that accelerated soil erosion is a problem in the catchment, resulting in high rates of sedimentation of the ‘Muela Reservoir. This erosion is blamed on the over-stocking of rangelands which leads to overgrazing and development of bare soil cover.